Partisipasi Masyarakat dalam Penanaman Mangove untuk Meningkatkan Ekowisata di Kelurahan Klawalu Kota Sorong - Murni; Kadir, Muhammad Arifin Abd; Abu, Nur; Ibal, La (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Klawalu Mangrove Ecotourism, a mangrove forest area in Sorong City, Southwest Papua, has great potential as a significant tourist destination. Therefore, increasing community involvement in mangrove planting is very important to support ecotourism development. Ecotourism not only provides natural entertainment to tourists but also aims to enable tourists to actively participate in environmental conservation efforts. Apart from that, it is also hoped that tourists will gain a deep understanding of the complexity of the environment, forming an awareness of the importance of preserving the region, both now and in the future. This service aims to increase community participation in planting mangroves to improve ecotourism in Sorong City. With this service, it can increase public awareness of the importance of an educational, green, and clean environment and strengthen community initiatives to protect, maintain, and improve the function of the environment. So with mangrove ecotourism, the welfare of local communities can increase. Through the implementation of ecotourism, it is hoped that opportunities will be created for the growth of MSMEs.